PENGEMBANGAN LKS BERBASIS PROJECT BASED LEARNING PADA MATERI ELEKTROLIT DAN NON ELEKTROLIT KELAS X SMA - Klaudius Ware; Sri Sulistyaningsih N.D. Tiring; Faleria Bonafasia Dei (Universitas Labuhanbatu, 2022)
This study aims to determine the development procedure and feasibility level of project based learning worksheets on Electrolyte and Non-Electrolyte Materials for the Tenth Grade High School Students. The study was conducted at SMAS St. Gabriel Maumere and SMAK St. Petrus Kewapante.Â This type of research was in the form of research and development by following the Borg and Gall model. The instruments used in this study were validation sheets and feasibility questionnaires. The subjects in this study who involved in the first phase of the trial were 10 students of class X MIA with one chemistry teacher. The second phase of the trial were 30 students of class X MIA with two chemistry teacher, and the trial were 60 students of class X MIA and involved two chemistry teacher. The results showedÂ that project based learning Worksheets development was feasibleÂ to be used in chemistry learning.